Molecular Basis for Defining the Pineal Gland and Pinealocytes as Targets for Tumor Necrosis Factor - Carvalho-Sousa, Cláudia E.; da Silveira Cruz-Machado, Sanseray; Tamura, Eduardo K.; C. M. Fernandes, Pedro A.; Pinato, Luciana; Muxel, Sandra M.; Cecon, Erika; Markus, Regina P. (Frontiers in Endocrinology, 2011)
The pineal gland, the gland that translates darkness into an endocrine signal by releasing melatonin at night, is now considered a key player in the mounting of an innate immune response. Tumor necrosis factor (TNF), the first pro-inflammatory cytokine to be released by an inflammatory response, suppresses the translation of the key enzyme of melatonin synthesis (arylalkylamine-N-acetyltransferase, Aanat). Here, we show that TNF receptors of the subtype 1 (TNF-R1) are expressed by astrocytes, microglia, and pinealocytes. We also show that the TNF signaling reduces the level of inhibitory nuclear factor kappa B protein subtype A (NFKBIA), leading to the nuclear translocation of two NFKB dimers, p50/p50, and p50/RelA. The lack of a transactivating domain in the p50/p50 dimer suggests that this dimer is responsible for the repression of Aanat transcription. Meanwhile, p50/RelA promotes the expression of inducible nitric oxide synthase (iNOS) and the production of nitric oxide, which inhibits adrenergically induced melatonin production. Together, these data provide a mechanistic basis for considering pinealocytes a target of TNF and reinforce the idea that the suppression of pineal melatonin is one of the mechanisms involved in mounting an innate immune response.